Marked systemic necrotizing disease in a Leptodactylus vastus (Anura: Leptodactylidae) from an urban reserve in northeastern Brazil - Braga, Roberta da Rocha; Eleutério, Bruna Kassia Nunes; Lima, Renan Carlos de Souza; Quirino, Tatiana Feitosa (Brazilian Journal of Veterinary Pathology, 2023)
The decline of amphibian populations concerns scientists worldwide and has been related to the spreading infectious diseases, among other environmental factors. Acute mass mortality with hemorrhagic and necrotic lesions has been described and associated with wild amphibian viruses. These diseases were first recorded in Central America and Australia in the early 1990s and later in Brazilian Atlantic Forest fragments. Epizootiological data on these infections must be included in other Brazilian phytogeographic regions and domains. This work aimed to report a systemic necrotic morbid state in a native Leptodactylus vastus from an urban reserve in northeastern Brazil, describing clinical and pathological findings and discussing its importance and likely etiologies. An adult L. vastus presented an erythematous oral cavity with multifocal point-like erosions, sublingual congested vessels, oropharyngeal edema, and mild esophageal mucosal prolapse. After therapeutic protocol, the patient showed no improvement; then, he was humanely euthanized. Necropsy demonstrated moderate to marked multicentric chronic necrotizing lesions. Histopathology revealed diffuse necrotic tissues with a few intracytoplasmic amphophilic inclusions in cellular remnants, with minor hemoparasites, helminths, and bacterial granulomatous coinfections. Clinical and pathological findings suggested a major chronic viral infection with minor coinfections. In the current case, confirmation of etiology struggled with financial and logistic limitations. Future partnerships will enable definitive diagnostics. This is the first record of systemic necrotizing disease in a wild frog in Ceará state, northeastern Brazil, and it is a red flag to emerging infectious diseases surveillance in this geographic area.